The many daughters of Afong Moy : a novel [compact disc, unabridged] - Ford, Jamie (Simon & Schuster Audio, 2022)
When Dorothy Moy discovers her daughter may suffer from the same debilitating depression that she does, she seeks radical help and endeavors to break the cycle of pain and find peace.